Persuading the Tortoise. (20th May 2015) - Marconi, Diego
Abstract: In On Certainty, Wittgenstein addressed the issue of beliefs that are not to be argued for, either because any grounds we could produce are less certain than the belief they are supposed to ground, or because our interlocutors would not accept our reasons. However, he did not address the closely related issue of justifying a conclusion to interlocutors who do not see that it follows from premises they accept. In fact, Wittgenstein had discussed the issue in the Remarks on the Foundations of Mathematics ; his view had been that certain inferential practices are constitutive of our notions of thinking and inferring. I argue that his treatment of unfounded beliefs in On Certainty essentially replicates, mutatis mutandis, his treatment of basic logical inference.